Assessing the effect of school bullying prevention programs on reducing bullying - EROL, SAİME (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This study was conducted for the purpose of assessing the effects on reducing bullying of a school bullying prevention program (BPP). A pre-test/post-test and control group, semi-experimental design was used for the research. The universe and sampling for the study comprised 583 pupils, ages 12-15, enrolled in two elementary schools in Istanbul. The BPP was prepared in accordance with the Behavioral-Ecological Model (BEM) and the Neuman Systems Model (NSM) and it encompassed faculty members, families and students. In the post-test, the mean scores of the study group in all of the sub-scales of the Peer Victimization Scale (PVS) and in the threatening/intimidating sub-scale of the Peer Bullying Behavior Scale (PBBS) were found to be significantly lower than those of the control group (p < .05). It was concluded that the BPP organized in line with the BEM and the NSM was effective in reducing bullying and could be used in nursing practices. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: School health; Peer bullying; School bullying prevention program; School health nursing; STUDENTS; HEALTH; BEHAVIORS; MODEL